THE INTEGRATION OF PSYCHOECONOMICS IN HEALTHCARE DECISIONMAKING: A THEORETICAL FRAMEWORK - Maria Cati, Matteo (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
This paper explores the integration of psychoeconomic principles in healthcare decision-making processes. Psychoeconomics, an interdisciplinary field combining psychological insights with economic theories, offers valuable tools for understanding and improving healthcare decisions. The study delves into key psychoeconomic concepts, their application in healthcare, and illustrates these ideas through detailed mind maps and graphs. Finally, a hypothetical case study is presented to demonstrate the practical application of these principles in a real-world scenario, highlighting the need for empirical research to validate theoretical predictions. The methodologies outlined provide a framework for future empirical studies.